Bilayers as Basic Formation of Epimolecular Structure of Mostly Lyotropic (Hydrotropic) Structuralized Liquid Systems Being Influenced Predominantly by the Temperature - Miloslav Milichovský (MDPI AG, 2022)
The bilayer's formations of amphiphilic molecules or polyions of different ionogenity comprise the basic building units of most organic biological and non-biological systems. A theory has evolved to explain their behaviour during the creation of those organized structures, such as anisotropic liquid crystal (LC) in lyotropic (especially hydrotropic) systems and polyelectrolyte multilayer (PEM) assemblies. Particular attention has been paid to the temperature and the important role of water in the formation and behaviour of the bilayers. A novel insight into the formation of hydrotropic liquid LC systems and their thermotropic behaviour is presented. In this context, the systems PEM assemblies are also discussed. Essentially, a structuralised form of water fills out continuous and discontinuous, i.e., confined, nano-spaces among hydrophilic interfaces of bilayers, controlling their supramolecular structure through a system of attractive and repulsive hydration forces. The character of those sophisticated bonding hydration systems is predestined by the composition and type of these hydrophilic interface groups. The miscellaneous complexity of the bilayer's aqueous systems suggests the need to study these examples in greater detail. Therefore, the bilayer's processes connected with disruption as far as destruction of bilayers are mentioned, i.e., the processes with the highest potential to combat bacteria, fungi, and viruses, such as in a situation where a person exhales a breath of micro-droplets containing virus nanoparticles (e.g., the COVID-19 virus).